Identification and Modeling of Factors Affecting the Effectiveness of Internal Auditing and Its Impact on Financial Reporting Quality Considering the Role of Organizational Culture - Hatami, Mohammad Bagher; Saedi, Rahman; Rahimi Dasjerdi, Mohsen; Mohammadi Khoshouei, Hamzeh (Management Strategies and Engineering Sciences, 2025)
The primary objective of this study is to identify and model the factors influencing the effectiveness of internal auditing and its impact on financial reporting quality, taking into account the role of organizational culture. This research is exploratory in nature and is classified as applied research in terms of its purpose. The statistical population consists of 179 managers from listed and over-the-counter (OTC) companies in Iran. Data collection was conducted using interviews and questionnaires, while hypothesis testing employed inferential statistics and structural equation modeling. The findings indicate that, in order of influence, organizational structure, risk management, audit committee, board of directors and executives, accounting information systems, working relationships (interactions) between internal and external auditors, independence, ethical courage, technological capabilities, professional commitment, auditor competence, and internal control have the most significant impact on the effectiveness of internal auditing. Moreover, the results demonstrate that both the effectiveness of internal auditing and organizational culture have a positive effect on financial reporting quality. Additional findings reveal that organizational culture does not have a moderating effect on the relationship between the effectiveness of internal auditing and financial reporting quality.